The small molecule hyperphyllin enhances leaf formation rate and mimics shoot meristem integrity defects associated with AMP1 deficiency - Poretska, Olena; Yang, Saiqi; Pitorre, Delphine; Rozhon, Wilfried; Zwerger, Karin; Castellanos Uribe, Marcos; May, Sean; McCourt, Peter; Poppenberger, Brigitte; Sieberer, Tobias (American Society of Plant Biologists, 2016)
ALTERED MERISTEM PROGRAM1 (AMP1) is a member of the M28 family of carboxypeptidases with a pivotal role in plant development and stress adaptation. Its most prominent mutant defect is a unique hypertrophic shoot phenotype combining a strongly increased organ formation rate with enhanced meristem size and the formation of ectopic meristem poles. However, so far the role of AMP1 in shoot development could not be assigned to a specific molecular pathway nor is its biochemical function resolved. In this work we evaluated the level of functional conservation between AMP1 and its human homologue HsGCPII, a tumour marker of medical interest. We show that HsGCPII cannot substitute AMP1 in planta and that an HsGCPII-specific inhibitor does not evoke amp1-specific phenotypes. We used a chemical genetic approach to identify the drug hyperphyllin (HP), which specifically mimics the shoot defects of amp1, including plastochron reduction and enlargement and multiplication of the shoot meristem. We assessed the structural requirements of HP activity and excluded that it is a novel cytokinin analogue. HP-treated wild-type plants showed amp1-related tissue-specific changes of various marker genes and a significant transcriptomic overlap with the mutant. HP was ineffective in amp1 and elevated the protein levels of PHAVOLUTA, consistent with the postulated role of AMP1 in miRNA-controlled translation, further supporting an AMP1-dependent mode of action. Our work suggests that plant and animal members of the M28 family of proteases adopted unrelated functions. With HP we provide a novel tool to characterize the plant-specific functions of this important class of proteins.